Building social capital for development: the role of religious values and virtues - Abdulai, Abdul-Mumin (Tughra Books, 2012)
This paper investigates the benefits that religious values and virtues can bring to bear on building social capital for societal development. From the outset, it has to be acknowledged that the majority of world's religious beliefs and practices are resting largely on an appreciable amount of values and virtues. Religious teachings such as respect for human life, the elderly, women, care for children, the destitute, etc. are fundamental virtues and values underpinning the articles of faith of almost all the world's religions including the so-called primitive religions. With that in mind, the paper sets out to examine the benefits of religion-as an embodiment of values and virtues-to society in terms of how people are galvanised into a cohesive and integrated group conducive for building social capital through social contacts and networking.